Enhanced thermal stability and flame retardancy of PLA through intumescent flame retardant with B-modified ZSM-5 as a synergistic agent - Xiaokun Zhai; Qin Ma; Jing Lu; Yuwei Jin; Ruiyan Zhang; Faliang Luo (eXPRESS Polymer Letters, 2024)
In order to improve the inherent flammability of polylactic acid (PLA) and make this new biodegradable material more widely used, B-modified ZSM-5 (B/Z5) was designed as synergistic agent of intumescent flame retardant (IFR), composed of ammonium polyphosphate (APP) and pentaerythritol (PER), and introduced into PLA/IFR (PLAs) to fabricate PLAs/B/Z5 composites by melt extrusion. The flame retardancy, surface morphology, and thermal stability of the composites were investigated by TG, LOI, UL-94, CCT, and SEM. The addition of B/Z5 makes the decomposition temperature of T5% as well as T10% of PLAs reduction in nitrogen atmosphere and carbon layer form in advance. UL-94 test shows the composites reach V-0 rating. LOI value also steadily increases, and the maximum value is 36.0% with B actual loading of 5.26% (recoded as 14B/Z5) in B/Z5. The PHRR decreases by 75% from 417.77 kW/m2 for pure PLA to 103.19 kW/m2 for PLAs/14B/Z5, and THR reduces from 92.78 to 19.26 MJ/m2, which decreases by about 80% and the char yield reaches 50%. This study provides a simple and green method for the preparation of high flame-retardant PLA, which has a broad practical application prospect.